Factors that affect the implementation of cooperative learning in public education institutions - Porras-Núñez, Mariela (2016)
This work presents the experience of training a group of high school English teachers from public schools, who learn and incorporate cooperative learning as a teaching methodology in the process of language teaching, since it has been found a low implementation of this approach in the classroom. The training was conducted through our virtual classroom (UNA Virtual), so teachers could receive a quality professional tutoring without the necessity to commute and attend to the classes in person. The modules covered: theoretical aspects of cooperative learning, cooperative learning strategies and design of cooperative activities adapted to MEP’s curriculum. Once the training concluded, our high school teachers were asked about the actual implementation of cooperative learning strategies in their classrooms to substantiate and assess the training received. Time and lack of resources hampered the corresponding implementation in a significant number of teachers; however, other teachers succeeded specifically with those language skills that needed more practice. The viewpoints of this group of teachers are presented here with the objective of foretelling difficult situations that may arise in the educational process.